Understanding the Warm Water Volume Precursor of ENSO Events and its Interdecadal Variation - S. Neske; S. McGregor (Geophysical Research Letters)
Abstract A wind forced ocean model is used to decompose the equatorial Pacific warm water volume (WWV) between 1980 and 2016 into two components: the (i) adjusted wind response, which is found by letting the model evolve unforced for three months, and (ii) instantaneous wind response, which are the instantaneous WWV changes due to Ekman transports. Our results suggest that roughly half of WWV variability is only as predictable as the winds that drive the instantaneous change. Separate examinations of pre‐2000 and post‐2000 periods reveal (i) nearly equal importance of instantaneous and adjusted responses for the pre‐2000 period and (ii) dominance of the instantaneous response during the post‐2000 period, which is most apparent during the recharged phase. This increasing instantaneous contribution prominence explains the post‐2000 reduction in WWV/El Niño‐Southern Oscillation sea surface temperature lead times (from six to nine months pre‐2000 down to three months post‐2000) and is consistent with the reduction in post‐2000 El Niño‐Southern Oscillation prediction skill.